2020
DOI: 10.1177/0963689720903709
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Surgical and Cadaveric Intestine as a Source of Crypt Culture in Humans

Abstract: Human small intestinal crypts are the source of intestinal stem cells (ISCs) that are capable of undergoing self-renewal and differentiation to an epithelial layer. The development of methods to expand the ISCs has provided opportunities to model human intestinal epithelial disorders. Human crypt samples are usually obtained from either endoscopic or discarded surgical samples, and are thereby exposed to warm ischemia, which may impair their in vitro growth as three-dimensional culture as spheroids or enteroid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
(73 reference statements)
0
3
0
Order By: Relevance
“…Scale bar 50 μm be stored in cold saline/phosphate buffered saline (PBS) at 4 °C until crypt isolation [10]. A recent study successfully cultured crypt units from human tissue stored up to 144 H and had improved yields and subsequent growth if tissue was stored in a specialized, commercially available preservation solution (University of Wisconsin/UW Solution) [11]. It is unlikely that the majority of equine practitioners would have quick access to these specific preservation solutions which is why the authors chose to store the tissue in more readily and widely available PBS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Scale bar 50 μm be stored in cold saline/phosphate buffered saline (PBS) at 4 °C until crypt isolation [10]. A recent study successfully cultured crypt units from human tissue stored up to 144 H and had improved yields and subsequent growth if tissue was stored in a specialized, commercially available preservation solution (University of Wisconsin/UW Solution) [11]. It is unlikely that the majority of equine practitioners would have quick access to these specific preservation solutions which is why the authors chose to store the tissue in more readily and widely available PBS.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers in 2013 demonstrated that murine ISCs could be stored at 4 °C for up to 30 h (H) with comparable proliferative potential [10]. More recently, processed samples from human surgical biopsies and cadavers were stored for up to 144H in organ preservation solution and yielded both successful crypt isolation and ISC culture [11]. However, the culture of equine ISCs following delayed tissue storage has not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…This is particularly true for allogeneic grafts as hLECs usually come from cadaveric corneas that may have been stored in an eye bank for a long period of time. This could also be the case for intestinal stem cells and bone marrow hematopoietic stem cells that are sometimes isolated several hours to several days after the harvest of the tissue due to delays essentially related to shipment of samples to local research facilities [ 13 , 14 ]. For these tissues, both postmortem time (PMT) and storage time (ST) are therefore factors of great importance.…”
Section: Introductionmentioning
confidence: 99%